Development and Validation of an Item Bank for Drug Dependence Measurement Using Computer Adaptive Testing. - Liu, Siyang; Tu, Dongbo; Cai, Yan (Substance Use & Misuse, 2020)
Currently, measurement tools to assess patient-reported outcomes for drug dependence are limited in their latent trait to adapt to the needs of individual patients while also maintaining comparability of scores across patients. Purpose/Objectives: To develop an item bank for computer adaptive testing (CAT) to measure severity of drug dependence. Methods: There were four phases: (1) review the literature of drug dependence measurement; (2) formulate an item list to be assessed by experts; (3) pretest our item list in two substance dependence treatment centers; and (4) field-test and conduct psychometric performance analysis with the final item bank. Additionally, based on our response data, a CAT simulation was used to validate the item bank, Drug Dependence CAT (DD-CAT). Results: The final drug dependence item bank – with a unidimensional configuration – contained 56 items with good item-fit, high discrimination, no differential item functioning, and covered all symptoms of diagnostic criteria for drug dependence. These results revealed that the final item bank was of good quality. Additionally, the results of a simulation CAT procedure with real response data indicated that the DD-CAT item bank exhibited acceptable and reasonable test reliability, content validity, and criterion-related validity. Conclusions/Importance: The proposed item bank for DD-CAT contained acceptable reliability and validity, and exhibited a shorter but efficient assessment of drug dependence. These psychometric properties can result in shorter test times, less information loss, and a reduction in the testing burden of patients.